Potential Association of Reactive Oxygen Species With Male Sterility in Peach - Cai, Yaming; Ma, Zhishen; Ogutu, Collins Otieno; Zhao, Lei; Liao, Liao; Zheng, Beibei; Zhang, Ruoxi; Wang, Lu; Han, Yuepeng (Frontiers in Plant Science, 2021)
Male sterility is an important agronomic trait for hybrid vigor utilization and hybrid seed production, but its underlying mechanisms remain to be uncovered. Here, we investigated the mechanisms of male sterility in peach using a combined cytology, physiology and molecular approach. Cytological features of male sterility include deformed microspores and tapetum cells along with absence of pollen grains. Microspores had few cytoplastic organelles at the mononuclear stage and were compressed into belts and subsequently disappeared in the anther cavity, while tapetum cells were swollen and vacuolated, with a delayed degradation to flowering time. Male sterile anthers had a ROS burst and lower levels of major antioxidants, which may cause abnormal development of microspores and tapetum, leading to male sterility in peach. In addition, the male sterility appears to be cytoplasmic in peach, which could be due to sequence variation in the mitochondrial genome. Our results are helpfulfor further investigation of the genetic mechanisms underlying male sterility in peach.